Prospek Pengembangan Usahatani Kakao di Kecamatan Bandar Baru Kabupaten Pidie Jaya - M. Akbar, Rizky; Khumaira, Khumaira; Fitri, Sri (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2025)
Basically, a farming sector that is developed, especially cocoa plants, can cover all costs incurred to avoid losses. So, a field of farming that is carried out must make a profit for the farmer. Cocoa farming is worth pursuing if the profits obtained are greater than investment costs, which can be a reference in developing cocoa farming that is more efficient and produces higher productivity, quality and economic value if the farming is carried out. The aim of this research is to determine the feasibility of developing cocoa farming in terms of technical and financial aspects. The hypothesis derived is that the prospects for developing cocoa farming in Bandar Baru District, Pidie Jaya Regency are worthy of development in terms of technical and financial aspects. The object of this research is farmers who cultivate cocoa and the potential of their existing land. The data analysis model used is Net Present Velue (NPV), Net B/C Ratio, Internal Rate of Return (IRR). Research on interest rates of 18% obtained an NPV of Rp. 39,521,800, -. Cocoa farming is profitable because the NPV is greater than 0 (zero), cocoa farming is worthy of development. Net B/C Ratio 1.31 shows that profits are obtained when plants are producing, covering losses from plants that are not yet producing. The resulting IRR was 20.15%, meaning it was greater than the Discount Rate (18%) that was in effect at the time of the research, thus cocoa farming was feasible to develop.